KITOSAN-GELFOAM KULIT KAKAO SEBAGAI TERAPI LUKA PASCA EKSTRAKSI GIGI TIKUS WISTAR DENGAN TERAPI ANTIKOAGULAN - Astika Swastirani, drg., M.Si; Nurul Lail Adha Mutia (E-Prodenta Journal of Dentistry, 2023)
Background : Anticoagulants as prophylactic therapy in stroke patients have antithrombotic effect. Extraction of patient's with anticoagulant therapy causes prolonged bleeding. Local hemostatic agents required to stimulate coagulation formation and platelet aggregation. Chitosan gelfoam cocoa podhusk extract is a local hemostatic agent, accelerates hemostasis without affecting consumption of anticoagulants by facilitating proliferation of fibroblasts and lymphocytes, growth of granulation and epithelial tissue, and inducing bone proliferation. Phytochemical components of cocoa podhusk extract are proven contain alkaloids as potential antioxidants that can block reactive oxygen sepsis (ROS). Objective: to understand the effect of chitosan gelfoam cocoa podhusk extract in increasing lymphocytes in the tooth socket after extraction in male wistar rats with anticoagulant therapy. Methods: The study was conducted on 24 male Wistar rats with anticoagulant therapy divided into eight groups, a negative control group, a positive control group that was given oral tranexamic acid therapy, treatment group 1 with gelfoam chitosan therapy with 1ml cocoa peel extract, and the treatment group. 2 with 10 ml of chitosan gelfoam cocoa peel extract therapy. Animals were decapitated on the 3rd and 7th days, samples were taken and histology preparations were made. Histological observations were carried out using LC Micro software with the analyzes performed were One Way Anova, Post Hoc Turkey, Kruskal Wallis, and Mann Whitney. Results : Chitosan gelfoam cocoa podhusk extract at concentrations of 1.6% and 15% proved effective in replacing tranexamic acid as the gold standard for wound healing after tooth extraction with the most effective concentration of 15%. Keywords: chitosan, cocoa, anticoagulant, wound healing, lymphocytes